On the linguistic units co z tym fantem zrobić and coś z tym fantem zrobić – grammatical and textual issues - Wojdak, Piotr (Papers in Linguistics, 2026)
The article examines the units co z tym fantem zrobić and coś z tym fantem zrobić in terms of their grammatical structure and functioning in texts. Based on corpus data (NKJP [the National Corpus of Polish], KWJP [the Corpus of Contemporary Polish]), it discusses syntactic and inflectional variation related to the verbal component (subordinate infinitive, non-subordinate infinitive, finite forms), and in the case of the unit with co [what] – also the differences between interrogative-dependent and interrogative uses. Both phrasemes most often occur in infinitival variants. The variant with a non-subordinate infinitive, which clearly dominates for the unit with co, speaks in favour of its classification as a phrase, although rarer variants complicate such a categorization. The unit with coś [something] is easier to classify (as an expression) by relying on its potential for inflection rather than on its dominant subordinate infinitival use. Overall, the analysis shows vagueness or insufficiency of the traditional opposition between phrases and expressions (phraseological utterances and verbs), as well as specific difficulties in creating dictionary entries for units that display frequency-imbalanced grammatical variation. Expansions of the nominal component (adjectival, clausal) are treated as textual innovations which indicate its relative functional independence. The analysis of lexical combinability also showed the dominance of exponents of ignorance, them being external syntactic superordinates for the unit with co.